2013
DOI: 10.3389/fnins.2013.00079
|View full text |Cite
|
Sign up to set email alerts
|

The immune consequences of preterm birth

Abstract: Preterm birth occurs in 11% of live births globally and accounts for 35% of all newborn deaths. Preterm newborns have immature immune systems, with reduced innate and adaptive immunity; their immune systems may be further compromised by various factors associated with preterm birth. The immune systems of preterm infants have a smaller pool of monocytes and neutrophils, impaired ability of these cells to kill pathogens, and lower production of cytokines which limits T cell activation and reduces the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
260
2
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(285 citation statements)
references
References 123 publications
(154 reference statements)
8
260
2
15
Order By: Relevance
“…15 Previous studies in preterm infants have shown a reduced response to other conjugate vaccines, including those targeting H influenzae type b 16 and Neisseria meningitidis serogroup C. 17 These data, together with the increased risk of IPD in preterm infants, 2,18 highlight the need to ensure that preterm infants are immunized and respond adequately to vaccination against S pneumoniae.…”
Section: Discussionmentioning
confidence: 96%
“…15 Previous studies in preterm infants have shown a reduced response to other conjugate vaccines, including those targeting H influenzae type b 16 and Neisseria meningitidis serogroup C. 17 These data, together with the increased risk of IPD in preterm infants, 2,18 highlight the need to ensure that preterm infants are immunized and respond adequately to vaccination against S pneumoniae.…”
Section: Discussionmentioning
confidence: 96%
“…When compared with normal birth weight infants, VLBW infants were .2 times more likely to have CLABSI and nearly 3.5 times more likely to develop VAP. This may be due to decreased innate and adaptive immunity of VLBW infants 28 and higher rates of device utilization, the combination of which increases the risk of HAIs substantially. Despite these challenges, VLBW infants have been the subject of large-scale quality improvement efforts to reduce CLABSI over the past decade, and this likely contributes to the substantial reductions seen.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble proteins and peptides have the ability to opsonize pathogens and, in that way, directly kill them through their antimicrobial properties, thus limiting production of soluble factors, such as immunoglobulins (Ig). Low IgG levels result in a lack of opsonization, leading to deficiencies in phagocytosis [10]. Preterm infants have a reduced pool of neutrophils and monocytes, and their precursors (phagocytic cells), due to the diminished granulocyte colony-stimulating factor (G-CSF) and granulocyte-macrophage colony-stimulating factor (GM-CSF) levels [9].…”
Section: Discussionmentioning
confidence: 99%